Brain Metastases from Adult Sarcoma: Prognostic Factors and Impact of Treatment. A Retrospective Analysis from the French Sarcoma Group (GSF/GETO). (22nd June 2018) - Chaigneau, Loïc; Patrikidou, Anna; Ray‐Coquard, Isabelle; Valentin, Thibaud; Linassier, Claude; Bay, Jacques Olivier; Moureau Zabotto, Laurence; Bompas, Emmanuelle; Piperno‐Neumann, Sophie; Penel, Nicolas; Alcindor, Thierry; Laigre, Maryline; et al.
Abstract : Background: Brain metastases (BM) from adult soft tissue or bone sarcomas are rare, and sparse data exist on their prognostic factors and management. Subjects, Materials and Methods: A retrospective study was conducted in 15 centers of the French Sarcoma Group, plus one Canadian and one Swiss center, to report on clinical, histological, and treatment characteristics and to identify predictive factors of outcome. Results: Between 1992 and 2012, 246 patients with a median age of 50 years (range: 16–86) were managed for BM. BM included 221 cerebral and cerebellar metastases and 40 cases of meningeal sarcomatosis. The most frequent histopathological subtype was leiomyosarcoma (18.7%). Histological grade was high in 118 (48%) cases. Surgery of BM was carried out for 38 (15.5%) patients. Radiotherapy and chemotherapy were administered in 168 (68.3%) and 91 (37.0%) patients, respectively. Irrespective of treatment modality, BM were controlled in 113 patients (45.9%), including 31 partial responses (12.6%) and 18 complete responses (7.3%). The median overall survival from diagnosis of brain metastasis was 2.7 months (range: 0–133). In the multivariate analysis, the following parameters influenced overall survival: chemotherapy (hazard ratio [HR] = 0.38; 95% confidence interval [CI]: 0.26–0.48), surgery (HR = 0.40; 95% CI: 0.22–0.72), stereotactic radiotherapy (HR = 0.41; 95% CI: 0.19–0.90), whole‐brain radiotherapy (HR = 0.51; 95% CI: 0.35–0.76), and grade (HR = 0.65; 95% CI: 0.43–0.98). Conclusion: BM of sarcomas are rare and associated with a dismal outcome. Multidisciplinary management with chemotherapy, radiation therapy, and surgery is associated with a better survival. Implications for Practice: The incidence of brain and meningeal metastasis in bone and soft tissue sarcomas is estimated between 1% and 8%. Published data are derived from small retrospective case series, often in the pediatric population. A prognostic index is important to guide both clinical decision‐making and outcomes research, but one such is lacking for adult sarcoma patients with brain metastases. The current study describes brain metastasis in a large cohort of sarcoma patients. This study, conducted within the French Sarcoma Group, describes the natural history of sarcoma brain metastasis and enables the proposal of strategic recommendations for subsequent clinical trials and for the management of such patients. Abstract : This article reports the results of a study conducted within the French Sarcoma Group. The natural history of sarcoma brain metastasis is described, and strategic recommendations are proposed for the management of patients with sarcoma brain metastasis.